REVERSING AGING: PREVENTING AGE-RELATED DECLINE IN GLUTATHIONE AND MITOCHONDRIAL FUNCTION INCREASES LONGEVITY - Sekhar, R (Innov Aging, 2018)
Since mitochondria provide life-giving energy, impaired mitochondrial energetics which occurs in aging, could limit lifespan. Based on our prior discoveries that optimal mitochondrial fat-oxidation critically depends on adequate availability of the endogenous antioxidant Glutathione, and that Glutathione deficiency in aging can be corrected by dietary supplementation of N-acetylcysteine and glycine (NAC-Gly), we hypothesized that supplementing NAC-Gly in aging mice will prevent age-related Glutathione deficiency and mitochondrial decline, and thereby increase lifespan. We tested our hypotheses via two complementary studies in aging wild-type C57BL/6J mice: (1) To investigate longevity, we studied 32 mice matched for age and sex, supplemented from the age of 65-weeks with either a standard diet (in 16 control mice) or an isocaloric-isonitrogenous diet supplemented with NAC-Gly (in16 study mice). Results showed that NAC-Gly supplemented mice lived significantly (23.7%) longer than control mice (104.0+/-3.0 vs. 128.6+/-4.2 weeks, p<0.0001). (2) To investigate underlying mechanisms, we studied 16 mice aged 90-weeks in 2 groups (n=8 each) for 8-weeks. Both groups were matched for age, weight, and mitochondrial fat-oxidation. Control mice consumed a standard diet ad libitum. Study-mice were pair-fed an isocaloric-isonitrogenous diet supplemented with NAC-Gly, and significantly improved Glutathione (P<0.05), oxidative-stress (P<0.05), mitochondrial fat-oxidation (P<0.01), and molecular regulation of mitochondrial energy metabolism. These data highlight the exciting discovery of a new mechanism to increase longevity by supplementing NAC-Gly to prevent age-related Glutathione deficiency and thereby prevent impaired mitochondrial fatty-acid oxidation. Dietary supplementation of NAC-Gly could be developed as an innovative nutritional approach to improve health and longevity in elderly humans.